Approach to Suspected Li-Fraumeni Syndrome: A Case Report in Genetic Counseling and Multidisciplinary Management - Juliana Gozali; Sry Suryani Widjaja; Tanaka Tanaka; Sufida Sufida; Esther Reny Deswani Sitorus; Vito Filbert Jayalie; Hendrick Chandra; Marsal Risfandi; Perthyan Aulia Nasution; Sultana Faradz (Journal of Biomedicine and Translational Research, 2026)
Background: Li-Fraumeni Syndrome (LFS) is a rare autosomal dominant hereditary cancer predisposition syndrome resulting from germline mutations in the TP53 gene on chromosome 17p13. It significantly increases the risk of various early-onset cancers, making early detection and diagnosis of LFS vital. This study underscores the importance of genetic counseling and multidisciplinary management in addressing the needs of individuals and families affected by LFS and optimizing patient outcomes.Case Presentation: Case report of a 36-year-old male from Murni Teguh Hospital with suspected LFS, characterized by a rare and complex clinical course involving multiple primary tumors, glioblastoma multiforme (GM) and mandibular osteosarcoma (MO). Initial symptoms included a rapidly growing right mandibular mass, following neurological symptoms three months prior. Histopathological and immunohistochemical findings supported the diagnosis, with p53 overexpression indicating TP53 mutation. Family history and three generation pedigree revealed multiple early-onset cancers, fulfilling the criteria for suspected LFS.Conclusion: This case emphasizes the importance of genetic counseling and multidisciplinary management in diagnosing and managing suspected LFS. Proactive cancer surveillance and individualized care strategies are critical to mitigating risks and improving outcomes for patients and families affected by hereditary cancer syndromes.